The Neoliberalization of Creativity Education Democratizing, Destructing and Decreating - Kalin, Nadine M. (Creativity, Education and the Arts, 2018)
This book contemplates creativity education within the context of the neoliberal capitalist economy. In the current crisis of creativity, where we are required to be creative in an environment of entrepreneurialisation, the author analyses what creativity has become and what has been lost in various recent transitional periods. Calling for recommitment towards the politics of critical creativity for the public good, the author argues for an education that resists the ideologies of neoliberalism so that creativity may still be harnessed to rethink society. Inciting readers to conceive of alternate forms of creativity and associated education, this innovative book will appeal to educators, practitioners, creators and learners searching for inspiration beyond creative destruction. Nadine M. Kalin is Associate Professor of Art Education at the University of North Texas, USA. Her research intertwines post-political critique and contemporary art theories with philosophical and arts-based modes of inquiry in relation to education.